Analysis of Differences in Handling of Hajj Flights with Regular Flights on the Apron Unit Movement Control at The Airport International Adi Soemarmo - Rhamadhani, Adinda Ghita; Sutarwati, Sri (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Apron Movement Control officers have an important role in handling Hajj and regular flights. Handling Hajj flights is different from regular flights, Hajj flights require more handling, service and supervision than regular flights. This study aims to determine the differences in the handling of hajj flights and regular flights, the obstacles faced by Apron Movement Control (AMC) officers and the efforts made to overcome the obstacles encountered in hajj flights.The method used in this research is qualitative method. The data used in this study are primary data obtained by observing and interviewing and secondary data obtained from documentation. The data analysis process in this study uses Miles and Huberman's theory, namely collecting data, reducing data, presenting data, and drawing conclusions. Researchers tested the validity of this research data by using triangulation. The results of this study indicate that there are differences in the handling of hajj flights and regular flights, i.e. passengers are picked up on haj flights, differences in flight times, placement of parking stands, time slots for haj flights that cannot be determined, handling haj flights requires more cooperation between several units. Obstacles faced by AMC officers on hajj flights at Adi Soemarmo International Airport, namely vehicles transporting luggage and passengers of pilgrims who could not pass through the service road area, lack of human resources, and aircraft trouble. Efforts made by AMC unit officers so that the handling of regular flights and haj flights can run smoothly and effectively, namely by moving the parking stands for haj planes to become more accessible to the transportation of luggage and pilgrim passengers, AMC unit officers are able to optimize existing human resources in handling hajj and regular flights, for troubled aircraft the officers coordinate with the maintenance unit before passengers carry out the boarding process, so that haj flights and regular flights do not experience delays. Keywords : AMC officers, regular flights, Hajj flights.